Applicability of a colorimetric indicator label for monitoring freshness of fresh-cut green bell pepper - Chen, Hui-zhi; Zhang, Min; Bhandari, Bhesh; Guo, Zhimei (Postharvest biology and technology, 2018)
•pH dye-based indicator labels were studied for fresh-cut pepper spoilage assessment.•The microbial counts and sensory scores were correlated with in-package CO2.•Indicators responds via visible color change to CO2 in the package headspace.•This food freshness indicator label is suitable for intelligent packaging applications. Freshness is one of the main considerations for consumption and storage of fresh-cut products. In this study, a freshness indicator label of packaged fresh-cut green bell pepper has been constructed based on pH-sensitive indicators. Compared to indicator labels made by bromothymol blue alone, indicator label made by mixing methyl red and bromothymol blue solutions (at 3:2 proportion) with a concentration of 70 mL L−1 in indicator film solution (MB2 formula) could more clearly monitor pepper decay, where indicator label of MB2 type changed from yellow-green to orange. The label accurately responded to the pepper freshness by significant color change, due to the increased carbon dioxide concentrations in the package as a result of deterioration of pepper at chill temperature. Similarly the other parameters, such as aerobic plate count, weight loss, chlorophyll content, malondialdehyde content, membrane permeability and sensory scores, were also evaluated. The levels of these parameters reached the threshold of spoilage at days 7 at 7 ± 1 °C. Thus, the results showed that label made with a mixture of methyl red and bromothymol blue can be applied as an easy-to-use and promising indicator for freshness monitoring of packaged fresh-cut green bell pepper.